Variables affecting sulfasalazine - ion exchange resin complexation - Ameer Zuhair Wohaib; Nidhal Khazaal Maraie (College of Pharmacy / Mustansiriyah University, 2019)
The aim of this work is studying the effect of different variables on the loading of sulfasalazine on DEAE sephadex A 25 ion exchange resin as a carrier for systemic action. Different drug: resin complexes (resinate) of different ratios (2:1, 1:1, 1:2, 1:4, 1:6) were prepared, dionized distilled water used to prepare sulfasalazine solution, and their entrapment efficiency was estimated through changing variable conditions including temperature of stirring, stirring time, stirring speed, pH. The best complex was formed using 1:6 drug: resin ratio prepared at 50 ºC, stirring speed 400 rpm for 120 minutes in deionized water (pH 7). The prepared complex gave 77.8% drug release within 15 minute and continued up to 97.613% within 75 minute upon exchanging the drug with ions of similar charge in the dissolution medium (phosphate buffer pH 7.4).